International Media Misperceptions of Islam and Terrorism: A Social Constructionist Perspective (Jurnal Kajian Jurnalisme, 2026)
Background: For several decades, Islam and Muslims have frequently been associated with terrorism in international media, including films, despite the fact that Islam neither teaches nor endorses acts of terrorism. Purpose: This article seeks to clarify that Islam is not a religion that endorses terrorism or terrorist acts. More specifically, it explores the brief history of terrorism, elucidates the Islamic perspective on terrorism, and argues that terrorist acts may arise, in part, from negative media labelling by powerful actors. Methods: This study employs a desk-based research method. Results: The findings suggest that terrorism frequently emerges from political, social, or economic repression. Although some acts of terrorism have been perpetrated by groups identifying with religious causes, terrorism is not prescribed by any religion. Islamic teachings, in particular, explicitly condemn terrorism. However, when certain Muslim groups are labelled as terrorists, their reactionary behavior may stem from negative labelling and perceived unjust treatment. Such groups are often portrayed as terrorists by international media, including films, in response to their harsh reactions despite experiencing various forms of oppression. Conclusion: Islam does not endorse terrorism; therefore, acts of terrorism should not be attributed to the teachings of Islam or to Muslims as a whole. Implications: International media and Western countries—particularly the United States—should reevaluate their policies and adopt more balanced approaches toward Muslim communities by examining the underlying factors that motivate some groups to resort to terrorist methods out of frustration or desperation.